DYNAMICS ACCULTURATION AND APPRECIATION PHENOMENOLOGICAL ON FORM DANCE REJANG PANGASTUTI AT BHUANA SHANTI TEMPLE - Ni Luh Ade Puspa; Muhammad Jazuli (RADJA PUBLIKA, 2026)
Study This describe element form And analyze essence functional Dance Rejang Pangastuti as a sacred dance for the Balinese Hindu diaspora community in Bandar Lampung City. Through a hermeneutic phenomenological approach, this study explores the subjective experiences of artists and religious figures regarding the manifestation of cultural acculturation in room ritual. Data collected through interview deep, observation participatory in Pura Bhuana Shanti, and documentation studies. The results of the study indicate that the dance choreography This is synthesis from nine elementform dance Which accommodate cultural hybridization. Affirmation identity local Lampung manifest on infiltration varietymovement floating samber And lipeto, use cloth weaving obi but s patterned boat, as well as formation pattern geometryfloor Which form Siger Lampung. In a way phenomenological, dance This pure functions as a means of upakara (holy offering) which is experienced through adherence to the requirements of purity spiritual (cuntaka). Findings This concludethat acculturation in Dance Rejang Pangastuti is not merely an aesthetic experiment, but rather a cultural strategy to strengthen the sovereignty of identity and theological respect for new footholds without reducing the sacredness of ancestral heritage.